2006
DOI: 10.4161/cc.5.19.3340
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Activation of Tumor Suppressor MicroRNAs in Human Cancer Cells

Abstract: Previously published online as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/abstract.php?id=3340 KEY WORDSmicroRNA, DNA methylation, histone modification, epigenetic therapy of cancer ACKNOWLEDGEMENTSThis work was supported by grants from National Institute of Health grant RO1 CA 82422 (P.A.J.) and the Uehara Memorial Foundation of Japan (Y.S.). Perspective Epigenetic Activation of Tumor Suppressor MicroRNAs in Human Cancer Cells ABSTRACTMicroRNAs (miRNAs) are small non-coding RNAs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
162
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(165 citation statements)
references
References 23 publications
1
162
1
1
Order By: Relevance
“…26 The observation that miRNA genes can become aberrantly methylated in tumors now adds an additional layer of complexity to the effects of epigenetic deregulation in cancer. 27 The functional consequences of altered miRNA gene methylation on tumorigenesis can be illustrated by results from the studies discussed previously. Epigenetic reactivation of miR-127 resulted in downregulation of the BCL6 proto-oncogene, a transcriptional repressor that has been shown to be involved in p53 regulation.…”
Section: Functional Consequences Of Altered Mirna Gene Methylation Inmentioning
confidence: 99%
“…26 The observation that miRNA genes can become aberrantly methylated in tumors now adds an additional layer of complexity to the effects of epigenetic deregulation in cancer. 27 The functional consequences of altered miRNA gene methylation on tumorigenesis can be illustrated by results from the studies discussed previously. Epigenetic reactivation of miR-127 resulted in downregulation of the BCL6 proto-oncogene, a transcriptional repressor that has been shown to be involved in p53 regulation.…”
Section: Functional Consequences Of Altered Mirna Gene Methylation Inmentioning
confidence: 99%
“…Recent studies have indicated that aberrant expression of miRNAs contributes to the initiation and progression of human malignancies (Calin and Croce, 2006a, b). We have recently shown that some miRNAs are located near CpG islands and that expression of these miRNAs is regulated by alterations in DNA methylation and histone modification on their CpG islands (Saito and Jones, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that one mode of transcriptional silencing of microRNAs may be epigenetic mechanisms related to the aberrant DNA methylation of 5 0 -regulatory regions, as has been observed for many 'conventional' tumor suppressor genes (Toyota et al, 1999;Kondo and Issa, 2004;Kim et al, 2006). In fact, examples of DNA methylation-based regulation of microRNA genes by proximal CpG islands have been recently described (Saito and Jones, 2006;Brueckner et al, 2007;Lujambio et al, 2007).…”
Section: Introductionmentioning
confidence: 99%